Trends in Social Inequality in Overweight and Obesity Among Danish Infants, 2002-2022 - Lis Marie Pommerencke; Sanne Ellegård Jørgensen; Sofie Weber Pant; Rikke Rothkegel Carlsson; Camilla Thørring Bonnesen; Lene Kierkegaard; Mette Rasmussen; Michael Davidsen; Trine Pagh Pedersen (International Journal of Public Health)
ObjectivesThis study aimed to examine trends in relative and absolute social inequality in overweight/obesity among Danish infants born between 2002 and 2022.MethodsThe study applied yearly cross-sectional data on infants’ weight and length at age 6–10 months, n = 63,100. Data was linked with parental education from population registers. Social inequality was measured by OR, relative index of inequality (RII), and slope index of inequality (SII). Trend tests measured changes over time.ResultsNo difference in odds for overweight/obesity by parental education was observed between 2002 and 2004, but from 2005 social inequality in overweight/obesity was revealed. The OR for overweight/obesity ranged from 1.20 (95% CI: 0.76–1.89) to 2.31 (95% CI: 1.64–3.25) for infants of parents with lowest educational attainment. RII ranged from 0.78 to 0.41 (test for trend, p = 0.179) and SII ranged from −0.92 to −4.54 (test for trend, p = 0.026) indicating a persistent relative social inequality and an increase in absolute social inequality in overweight/obesity from 2002 to 2022, respectively.ConclusionThe study revealed persistent relative social inequality and increased absolute social inequality in overweight/obesity among Danish infants from 2002 to 2022.